FEASIBILITY ANALYSIS OF UBUD MARKET REVITALIZATION PROJECT - Widhiawati, Ida Ayu Rai; Sanjaya, I Putu Ari; Widiadnyana, Putu Egges (Jurnal Ilmiah Teknik Sipil, 2023)
Ubud Market is a famous traditional market for its Balinese art and crafts. The poor facilities of Ubud Market and the fire that occurred on March 24 2016 which scorched block A of Ubud Market were the reasons for the revitalization. Revitalization is for the physical improvement of the market. So people are interested again in shopping at traditional markets considering the benefits provided by traditional markets. The purpose of this study is to determine the feasibility of the investment related to the Ubud Market revitalization project. It was analyzed by technical, financial, and economic aspects . Analysis of technical aspects obtained a building height of 10.12 m > 15 m (feasible), KDB of 74% > 60% (not feasible), KLB of 1.88 <2.4 (feasible), KDH of 22% > 20% (feasible), the technical requirements of SNI 8152:2021 about People's Markets out of 34 requirements there was 32 points have fulfilled the requirements. Analysis of the financial aspect to determine the comparison between the benefits and costs of this project. From the analysis, the NPV results are - Rp. 89.904.582.521,18 < 0 (not feasible). The BCR value is 0.16 6 < 1 (not feasible). IRR value < MARR (not feasible). PBP value was 35 years 1.7 months > 20 years (not feasible). The results from the project's sensitivity analysis will be feasible when revenue increases by 550%. Analysis of economic aspects obtained ENPV results of Rp. 465.097.854.283,64 > 0 (feasible), BCR of 5.3 > 1 (feasible). EIRR 62.40% > 12% of MARR (feasible).